TINDAK PIDANA PEDOFILIA DITINJAU DARI PERSFERKTIF PERLINDUNGAN ANAK DI KOTA SAMARINDA - Kharisma Dwi Pertiwi Siwi (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Pedophilia is a sexual activity carried out by adults against minors, pedophilia perpetrators are currently experiencing an increase in violence against children, which also leads to the death of the victims. Not to mention other pedophile behaviors that were exposed to court, which made parents even more worried that the dangers of pedophilia were so easy to threaten the lives of each of their children.Legal sanctions against pedophiles are stipulated in Law Number 17 of 2016 concerning the second amendment to Child Protection, providing fresh air for the Indonesian people. This is because, in this law, it provides heavier and more sinister sanctions for perpetrators of sexual crimes in this law that guarantees that the perpetrators do not get a law that is too light in this law also talks about the protection of the form that can be provided to child victims of crime, including victims of pedophilia, among others: Counseling, Services, Medical Assistance, Legal Aid, Supervision, Prevention.Efforts to protect children need to be continuously strived for in order to maintain the welfare of children, considering that children are one of the valuable assets for national development in the future.Keywords: Pedophilia, Sanctions, Child Protection